2015
DOI: 10.3109/13813455.2014.1003566
|View full text |Cite
|
Sign up to set email alerts
|

An acute bout of exercise modulate the inflammatory response in peripheral blood mononuclear cells in healthy young men

Abstract: Increased mRNA transcription of inflammatory genes in PBMCs may contribute to increased level of inflammatory markers after an acute bout of exercise. The increased mRNA levels of GATA-3 and TXB21 may indicate that T cell lymphocytes are activated and secrete cytokines into the circulation. It needs to be further investigated if exercise changes the Th1/Th2 balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
3
28
1
3
Order By: Relevance
“…In addition to circulating plasma molecules, we also investigated PBMC gene expression response to exercise both because immune cells play a critical role in muscle damage repair and regeneration and as a system-wide marker of alterations in gene expression (Gjevestad et al, 2015; Philippou et al, 2012; Radom-Aizik et al, 2009; Ulven et al, 2015). Transcripts presented two main trajectories with up- and down-regulated genes reaching a maximum response at 2 min and rapidly returning to baseline within 30-60 min ( Figure 4a , Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to circulating plasma molecules, we also investigated PBMC gene expression response to exercise both because immune cells play a critical role in muscle damage repair and regeneration and as a system-wide marker of alterations in gene expression (Gjevestad et al, 2015; Philippou et al, 2012; Radom-Aizik et al, 2009; Ulven et al, 2015). Transcripts presented two main trajectories with up- and down-regulated genes reaching a maximum response at 2 min and rapidly returning to baseline within 30-60 min ( Figure 4a , Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…After 20 minutes of cycling at 50% of VO 2peak , a non-significant decrease was observed in TNF-α (4.5 to 4.2 picogram/milliliter [pg/ml]). With regard to vigorous intensity exercise, the study of Ulven et al 19 reported an increase in serum levels of TNF-α after 60 minutes of cycling at 70% of VO 2Max . These disparities between studies may be explained in part by differences in the exercise protocols adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Messenger RNA expression of genes involved in immune and T cell function (eg, interleukin (IL)-1β and IL-8) are upregulated following acute cycling exercise 37. It is plausible that interval but not continuous exercise induced a change in this gene expression.…”
Section: Discussionmentioning
confidence: 99%